GENETIC VARIABILITY IN INDIGENOUS COTTON (GOSSYPIUM ARBOREUM) OF NORTH EASTERN REGION - ROY, A. (Annals of Agricultural Research, 2014)
The research work was , undertaken to collect and evaluate arboreum cotton cultivars of N.E.Region of India.The germplasm exhibited significant variation for all the traits along with high estimates of genetic variability and its related parameters. Hence these germplasm could be considered as valuable source of genetic variability for future breeding purposes. Moreover, with the recent trends in globalization of market economy the breeders have to take utmost care for systematic collection, evaluation and maintenance of the indigenous germplasm for the benefit of the farmers and the country as a whole.